Upaya pembaharuan dalam pendidikan dan pengajaran Cece Wijaya, Djaja Djadjuri, A. Tabrani Rusyan ; editor, Tjun Surjaman, Wilson Nadeak - WIJAYA, Cece; A. Tabrani Rusyan; Djaja Djadjuri; Wilson Nadeak; Tjun Surjaman (Rosda Grup, 1992)
xi, 192 hlm ilus 24 cm